Influence of eicosanoid lipid mediators on macrophage innate immune functions - Peters-Golden, Marc (Henry Stewart Talks, 2014)
Mediator paradigms in innate immunity, Eicosanoids, Eicosanoids in antimicrobial immunity: Yin and Yang, The leukotriene synthetic pathway, Role of LTB4 in bacterial killing by AMs, Pathway for NFκB activation upon PRR ligation, Cross-talk between PRR and GPCR pathways?, Dectin-1, LTB4 enhances yeast binding via dectin-1, Basal dectin-1 expression depends on constitutive LTB4 generation, LTB4 enhances dectin-1-induced cytokine generation by elicited MΦ, Dectin-1 expression in MΦ depends on an LTB4-PU.1 axis, Pathway for NFκB activation upon TLR ligation, LPS-induced nuclear translocation of NFκB subunits requires endogenous LTB4/BLT1 signaling, 5-LO metabolism is required for MyD88-dependent NFkB activity in macrophages, 5-LO and LTB4 are required for basal MyD88 expression in macrophages, MyD88 expression is controlled by STAT-1 and SOCS1, SOCS1 siRNA restores MyD88 expression and LPS responsiveness in 5-LO -/- MΦs, PGE2 actions are context-dependent, PGE2 synthesis and signaling, Opposing actions of PGE2 vs. LTB4, Eicosanoid imbalance in states of immunosuppression